A hybrid experimental-numerical approach for load rating of reinforced concrete bridges with insufficient structural properties. Issue 6 (3rd June 2019) - Bagheri, Abdollah; Ozbulut, Osman E.; Harris, Devin K.; Alipour, Mohamad; Zare Hosseinzadeh, Ali
Abstract: This article presents a non-destructive approach for load rating of reinforced concrete bridges without structural plans. The approach is found on a hybrid method, which employs vibration and live load testing coupled with numerical simulation and model updating techniques, to converge on estimate of unknown structural parameters. The material properties of bridge and the amount of reinforcing steel for calculating the bending capacity of a bridge are determined through model updating results and nondestructive approaches. The updated model is then employed to determine load effects for calculating load rating factors, and these results are combined with live load test result to arrive at the bridge capacity, and ultimately the load rating. The method is validated by testing a skewed reinforced concrete slab bridge for load rating purposes. The bridge was instrumented with accelerometers and strain gages, and the responses of the bridge under vibration and quasi-static tests were measured. Results demonstrated that the proposed method is capable of determining the bridge capacity and load rating factor with good accuracy, and not only can be used for load rating of concrete bridges without structural information, but also can be useful in condition assessment of existing concrete bridge with available as-built information.